Practice of lifelong learning in technical and vocational education: A case of Islamic University of Technology - Hossain Khan, Md. Shadat (2010)
In a time of continuous economic, social and technological change, skills and knowledge become quickly out-of-date. People who have not been able to benefit from formal education and training must be given opportunities to acquire new skills and knowledge that will give them a second chance in life and at work. Providing all individuals with learning opportunities throughout their lives is an ambitious but necessary undertaking. An all- inclusive lifelong learning system calls for the mobilization of increased public and private resources for education and training and for providing individuals and enterprises with the incentives to invest in meeting their learning and skills development needs. This paper attempts to explore and present about Lifelong Learning in Technical and Vocational Education and its practice in Islamic University of Technology (IUT) which has a lot offer to the OIC member states and the world of work because it is responsive, flexible, promotes exchanges of ideas and it is set up in such a way that fosters teamwork as well as individual achievement and the immediate transfer of skills in the work setting that are playing a major role in the field of life long learning for the OIC member states.